The Influence of Yanbua Method in Learning Al-Quran at Junior High School - Dian Kusuma Wardani; Muhammad Abdul Rofiq (SCHOOLAR: Social and Literature Study in Education, 2021)
Reminding of the importance of the role of the Al-Qur'an in guiding and mobilizing human life, learning to read, understand and live the Al-Qur'an to be practiced in everyday life is an obligation for every Muslim. The purpose of this research is finding how the influence of the use Yanbu'a Method in Kyai Mojo Junior High School. In this study using a quantitative method, namely the one-sample t test, the research design conducted by the researcher was to observe the application of the Yanbua method and then examine its effects. The use of the Yanbua method in learning Al-Quran at SMP Kyai Mojo Jombang . Based on the results of hypothesis testing, namely one-sample t-test, it was found that the Asymp value. Sig (2-tailed) of 0.000 <0.05, so it can be said that there is a significant effect of the use of Yanbua method in learning Al-Qur'an at Kyai Mojo Junior High School. The highest score is 96 and the lowest score is 76, this shows that the use of this Yanbua method is quite successful, and also the students have high confidence in reading the Quran in very good voice aloud and follow the tone of the reading taught by teacher.